2017
DOI: 10.1002/jmri.25616
|View full text |Cite
|
Sign up to set email alerts
|

Elevated adiabatic T and T in articular cartilage are associated with cartilage and bone lesions in early osteoarthritis: A preliminary study

Abstract: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:678-689.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Recent studies have shown that AdiabT 1ρ is sensitive to both ex vivo enzymatic cartilage degradation and in vivo articular cartilage degradation in OA patients . More importantly, the AdiabT 1ρ is much less sensitive to the magic angle effect than both conventional CW‐T 1ρ and T 2 as demonstrated in previous bovine cartilage studies .…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies have shown that AdiabT 1ρ is sensitive to both ex vivo enzymatic cartilage degradation and in vivo articular cartilage degradation in OA patients . More importantly, the AdiabT 1ρ is much less sensitive to the magic angle effect than both conventional CW‐T 1ρ and T 2 as demonstrated in previous bovine cartilage studies .…”
Section: Discussionmentioning
confidence: 82%
“…For example, fibrillation of the cartilage surface that was not visible by eye could be observed using optical coherence tomography, and alterations in mechanical properties were discovered using atomic force microscopy (AFM) [7][8][9][10]. Additionally, loss of glycosaminoglycan (GAG) content and water retention could be detected by AFM or magnetic resonance imaging and Fourier transformed infrared imaging [11][12][13]. Quantitative polarized light microscopy has been employed to visualize collagen, taking advantage of collagen's birefringence [7,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since articular cartilage is not innervated, approximately 50% of the patients with radiological changes of OA are symptomatic; therefore, the treatment is based on symptoms rather than radiological changes. Even a successful CPA might have a minimal effect on symptoms, leading to patients being reluctant to adhere to a therapy that does not improve their symptoms [50].…”
Section: Mri Assessmentmentioning
confidence: 99%